Caracterización de la cadena logística de los pequeños productores de café en la provincia de Lengupá - Camacho Numpaque, Didiher Andrey (Universidad Antonio Nariño, 2021)
The purpose of this research is to characterize the logistics chain for small coffee producers in the Province of Lengupá, department of Boyacá, identifying the different links and actors involved in coffee logistics in this province. The failures detected in its operation and the relationship that exists between each of the different actors are also described. The institutional support offered by state entities and non-governmental organizations for the promotion of coffee cultivation is evaluated. When evaluating the effects of intermediation by product marketers in the study area, it is noted that they are not significant for an efficient performance of the logistics chain.